2018
DOI: 10.1111/jvim.15093
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of echocardiographic indices of left atrial morphology and function in dogs with myxomatous mitral valve disease

Abstract: BackgroundThe prognostic relevance of left atrial (LA) morphological and functional variables, including those derived from speckle tracking echocardiography (STE), has been little investigated in veterinary medicine.ObjectivesTo assess the prognostic value of several echocardiographic variables, with a focus on LA morphological and functional variables in dogs with myxomatous mitral valve disease (MMVD).AnimalsOne‐hundred and fifteen dogs of different breeds with MMVD.MethodsProspective cohort study. Conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 44 publications
7
43
0
Order By: Relevance
“…In line with the literature, we found that LA/Ao and E wave velocity are predictors of CD [35]. The increase in LA/Ao ratio and E-wave values corresponds to an increased risk of CD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with the literature, we found that LA/Ao and E wave velocity are predictors of CD [35]. The increase in LA/Ao ratio and E-wave values corresponds to an increased risk of CD.…”
Section: Discussionsupporting
confidence: 90%
“…In this study the MST of ACVIM C patients belonging to different therapeutic groups was in accordance with those reported in the literature, although the more complex therapeutic scheme (groups 2 and 3) was associated with a shorter survival time [5,13,35,36,37]. This is despite the fact that patients with more advanced DMVD need more complex cardioactive therapy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Various prognostic indicators have been investigated in dogs with MMVD, in particular using various echocardiographic techniques, and different clinical variables associated with cardiac mortality have been identified [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Among them, breed of dog, advanced age, and body weight (BW) � 20 kg, as well as degree of mitral valve pathology; left atrial (LA) and left ventricular (LV) dilation and dysfunction; increased LA pressure; right ventricular dysfunction; development of atrial fibrillation (AF) and pulmonary hypertension (PH); and increased concentration of circulating cardiac biomarkers (e.g., NT-pro-BNP) have been associated with a worse prognosis [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. On the contrary, use of several drugs, including ACE-inhibitors, pimobendan, and spironolactone has a proven positive effect both on the quality and duration of life in dogs with MMVD [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 2D-SMOD may be a better method for the estimation of LA volume, if the 3D-EC is not available. One study found the LA volume indices including LA maximal volume (LAVmax) and LA minimal volume (LAVmin) using the ALM was useful to predict survival time when cardiac-related death was only considered [50]. In this study, the LAVmax > 3.53 mL/kg indicated high mortality risk in dogs with MMVD.…”
Section: The Methods For Measurement Of Left Atrial To Aortic Root Ratmentioning
confidence: 67%